Child homicide in Ontario, Canada: comparing criminal justice outcomes - Johnson, Anna (International journal of law, crime and justice, 2023)
Child homicide remains responsible for a high number of child deaths despite decreasing in recent decades. Much of the research on child homicide has focused specifically on filicide or the broader characteristics of child homicide. Little research has examined whether the degree of intimacy between victims and perpetrators in child homicide cases may impact criminal justice outcomes. Focusing on 603 cases of child homicide between 1985 and 2018 in Ontario, Canada, this exploratory study compares the criminal justice outcomes of perpetrators with a familial relationship, non-familial relationship, and no prior relationship with the victim. Results show that familial perpetrators were less likely to be convicted of murder. Stereotypes about intimacy and violence that may impact criminal justice outcomes in child homicide cases are explored. Suggestions for future research on the effect of intimacy on criminal justice outcomes are highlighted, and policy implications are also discussed.